Embedding SDGs in Ethiopian Higher Education: Overcoming Challenges, Seizing Opportunities, and Forging Inclusive Pathways for Digital-Era Transformative Learning - Belay Sitotaw Goshu; Melaku Masresha Woldeamanueal (BIRCU, 2026)
This study explores the integration of sustainability and global citizenship in Ethiopian higher education institutions (HEIs) through human-centered strategies and actionable recommendations. Across 12 institutions, including Hawasa and Jigjiga, six strategies, such as